Aerosol Retention Characteristics of Barrier Devices. (January 2021) - Fidler, Richard L.; Niedek, Christopher R.; Teng, Justin J.; Sturgeon, Mary E.; Zhang, Qi; Robinowitz, David L.; Hirsch, Jan
Abstract : Background: Disease severity in coronavirus disease 2019 (COVID-19) may be associated with inoculation dose. This has triggered interest in intubation barrier devices to block droplet exposure; however, aerosol protection with these devices is not known. This study hypothesized that barrier devices reduce aerosol outside of the barrier. Methods: Aerosol containment in closed, semiclosed, semiopen, and open barrier devices was investigated: (1) "glove box" sealed with gloves and caudal drape, (2) "drape tent" with a drape placed over a frame, (3) "slit box" with armholes and caudal end covered by vinyl slit diaphragms, (4) original "aerosol box, " (5) collapsible "interlocking box, " (6) "simple drape" over the patient, and (7) "no barrier." Containment was investigated by (1) vapor instillation at manikin's right arm with video-assisted visual evaluation and (2) submicrometer ammonium sulfate aerosol particles ejected through the manikin's mouth with ventilation and coughs. Samples were taken from standardized locations inside and around the barriers using a particle counter and a mass spectrometer. Aerosol evacuation from the devices was measured using standard hospital suction, a surgical smoke evacuator, and a Shop-Vac. Results: Vapor experiments demonstrated leakage via arm holes and edges. Only closed and semiclosed devices and the aerosol box reduced aerosol particle counts (median [25th, 75th percentile]) at the operator's mouth compared to no barrier (combined median 29 [−11, 56], n = 5 vs . 157 [151, 166], n = 5). The other barrier devices provided less reduction in particle counts (133 [128, 137], n = 5). Aerosol evacuation to baseline required 15 min with standard suction and the Shop-Vac and 5 min with a smoke evacuator. Conclusions: Barrier devices may reduce exposure to droplets and aerosol. With meticulous tucking, the glove box and drape tent can retain aerosol during airway management. Devices that are not fully enclosed may direct aerosol toward the laryngoscopist. Aerosol evacuation reduces aerosol content inside fully enclosed devices. Barrier devices must be used in conjunction with body-worn personal protective equipment. Abstract : In studies evaluating multiple systems, only closed devices, semiclosed devices, and aerosol boxes reduced exposure to aerosol particle counts. As a result, barrier devices must be used in conjunction with body-worn personal protective equipment.Supplemental Digital Content is available in the text.